The Effect of Investment Motivation, Return, and Risk Perception on Stock Investment Decision-Making Among Investors in Pontianak City - Salsabila, Putri Aurora; Hariyanto, Dedi; Safitri, Heni (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of investment motivation, return, and risk perception on stock investment decision-making among investors in Pontianak City. The method used is associative with a sample of 150 respondents selected using purposive sampling. The instruments were tested for validity, reliability, and classical assumptions such as normality, linearity, and multicollinearity. Data analysis used multiple linear regression, correlation tests, determination coefficients, and simultaneous and partial tests. The results of the multiple linear regression indicate that the three independent variables positively contribute to stock investment decisions. The correlation coefficients show a strong relationship between investment motivation, return, and risk perception with investment decisions. The coefficient of determination indicates that most of the variation in investment decisions can be explained by the three variables, while the rest is influenced by factors outside this study. Simultaneous tests show a significant combined effect of investment motivation, return, and risk perception on stock investment decisions. Partial tests indicate that investment motivation, return, and risk perception each have a positive and significant effect on stock investment decisions. This study confirms the importance of motivation, return expectations, and risk perception in determining investor decisions in the stock market in Pontianak.